Cross-Border Arbitration in Indonesia: Between International Arbitration Commitments and Domestic Judicial Practice - Annisa Putri Sinaga; Annisa Putri Andini Tanjung; Siti Salmiah Dalimunthe; Rahman Al Fauzi Siregar; Khotibul Umam (ISNU Sumatera Utara, 2026)
This paper examines the trends, legal challenges, and effectiveness of cross-border arbitration in Indonesia within the context of contemporary international trade and investment. The rapid growth of global commerce necessitates reliable dispute resolution mechanisms, positioning international arbitration as a preferred alternative due to its neutrality, procedural flexibility, and enforceability under instruments such as the 1958 New York Convention. Using a normative juridical approach, this study analyzes primary and secondary legal sources, including statutory regulations, scholarly literature, and arbitral decisions, through systematic stages of data collection, analysis, and synthesis. The findings reveal that while Indonesia possesses a solid legal framework for arbitration, practical challenges persist, including inconsistent judicial interpretations, limited institutional capacity, high procedural costs, and deficiencies in arbitration clause drafting. These factors affect the effectiveness and credibility of international arbitration. The study argues that the principal challenge does not lie in the inadequacy of Indonesia's arbitration legislation, but rather in the inconsistent interaction between domestic judicial practice and international arbitration commitments. It contributes to the existing literature by proposing a harmonized interpretative framework that reconciles national judicial sovereignty with Indonesia's obligations under the New York Convention, thereby strengthening legal certainty in cross-border commercial dispute resolution.